1937
DOI: 10.1007/bf01492271
|View full text |Cite
|
Sign up to set email alerts
|

Weitere Atomumwandlungen durch γ-Strahlen

Abstract: Heft I2. ] x9. 3. x937] Dieser bisher nur in der Theorie bekannte ProzeB miil3te sich, 5~flich wie dies hier bei STRb--S7Sr gesehehen ist, dutch massenspektrographische Untersuchung z. B. eines Indiumpr/iparates, das aus geologiseh altem Zinnvorkommen gewonnen wurde, naehweiseI~ lassen. Zum SehtuB sei den H e r r e n ¥ . HAUK und H. LICHTBLAU herzliehst gedankt, deren Eifer zum nieht geringen Teile die gut gelungenen Aufnahmen zu danken sind. Wien, Vereinigtes I. und II. Physikalisches Institut der Universit~i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 4 publications
3
24
0
Order By: Relevance
“…The product nucleus, Ta 180 , goes over to Hf 180 largely by K electron capture; in this process either γ rays are emitted or by their internal conversion extranuclear electrons ejected." This half-life agrees with the presently adopted value of 8.152(6) h. Previously, Pool et al reported a half-life without a mass assignment [38] and the 20 min half-life measured by Bothe and Gentner [39] was evidently incorrect. 181…”
Section: 177 Tasupporting
confidence: 84%
“…The product nucleus, Ta 180 , goes over to Hf 180 largely by K electron capture; in this process either γ rays are emitted or by their internal conversion extranuclear electrons ejected." This half-life agrees with the presently adopted value of 8.152(6) h. Previously, Pool et al reported a half-life without a mass assignment [38] and the 20 min half-life measured by Bothe and Gentner [39] was evidently incorrect. 181…”
Section: 177 Tasupporting
confidence: 84%
“…It was excited by shining a beam of photons on a target ( [78,79], see also [80][81][82]). Even before then, it was recognized [83] that a mean excitation frequency for dipole absorption could be derived from the nuclear polarizability with the help of the symmetry energy in the mass formula [84].…”
Section: Soft E1-modes and Pairingmentioning
confidence: 99%
“…This half-life agrees with the presently adopted value of 21.03(5) h. The previous assignment of the 17 h half-life to 112 Pd [33,34] mentioned in the quote was credited with the discovery of 112 Pd because it was due to a mixture of two isotopes. 113…”
Section: Pdmentioning
confidence: 99%
“…In the 1954 article, "A new isotope of palladium, 1.5-minute Pd 113 ", Hicks and Gilbert described the observation of 114 Pd and an isomeric state of 115 Pd, respectively. 116…”
Section: Pdmentioning
confidence: 99%